Pemilihan Jajanan Sehat terhadap Pengetahuan Anak SD Asisi Katolik Medan - Pomarida Simbolon; Agnes Louise Lasmaida; Febrina Br Sembiring; Mitra Amelia Ndruru; Theresia Elen Novia Ziraluo (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Abstract School snacks are one of the issues that need to be addressed by society, especially parents, educators, and school administrators. These snack foods are prepared and sold by street vendors on the streets or in public places and are eaten or consumed immediately. Generally, snack foods are ready-to-eat foods. Healthy snacks are foods that have the following characteristics: Free from flies, ants, cockroaches, and other animals that can carry germs; Free from dirt and dust; Foods that are steamed, boiled, or fried using sufficient heat, meaning not half-cooked; and Served using clean plates that have been washed with clean water beforehand. This research aims to maintain and improve overall body health, especially regarding healthy snacks at ASISI CATHOLIC ELEMENTARY SCHOOL MEDAN. This research uses an educational design. The research was conducted in April 2025. The results of this study show that almost all elementary school children are aware of what healthy snacks they can consume or eat every day. In this case, ASISI CATHOLIC ELEMENTARY SCHOOL MEDAN has implemented and carried out healthy snacks by requiring elementary school children to bring food from home.